Renewable and Non-renewable Energy Consumption, CO2 Emissions, and Responsible Economic Growth with Environmental Stability in North America - Mendoza-Rivera, Ricardo Jacob; García-Pérez, Luis Enrique; Venegas-Martínez, Francisco (International Journal of Energy Economics and Policy, 2023)
This paper examines the impact of the consumption of non-renewable energies (gasoline and gas), as well as the consumption of renewable energies (solar and wind) and CO2 emissions (one of the main pollutants) on Economic Growth (EG) in North America. The data comes from the public sources of the World Bank and British Petroleum annually from 1966-2020. A Vector Autoregressive (VAR) model is estimated to analyze relationships among the variables under study. Likewise, tests to confirm the non-presence of serial correlation in the residuals of the VAR are carried out. Subsequently, Granger causality tests and an analysis of impulse-response functions are performed. The EG for Canada is explained by a lag from the previous year with a small positive effect. Likewise, the Consumption of Non-Renewable and Renewable Energies (CNRARE) similarly affects EG in a slightly negative way and CO2 emissions are not significant to explain EG. The US and Canada share similar dynamics concerning CNRARE, but the CO2 emissions that accompany the industry do positively affect growth. Mexico differs from Canada and US in that the consumption of non-renewable energy (NRE) has a positive effect on economic growth, although it is not significant, and CO2 emissions negatively affect EG. This is due to a timeless change in industrial development that US and Canada went through previously in their process of industrialization and technological modernization. Finally, in Mexico and Canada, unlike US, a positive response from the EG is observed due to a shock from renewable energy. This investigation differs from current literature in the following: 1) many studies have been carried out on the subject in many countries and regions, but none have addressed the case of North America, to the extent that the authors are aware, 2) conducts an assessment of responsible growth with environmental stability in North America, and 3) provides public policy recommendations to promote the use of renewable energy in all sectors of production while respecting the environment in the long term.